Evaluation chain management model with emphasis on intellectual capital using blockchain technology - Mohammad Reza Zahedi; Morteza Piri (goodwood publishing, 2023)
Purpose: The main purpose of this paper is the evaluation of the chain management model with an emphasis on intellectual capital in knowledge-based organizations using blockchain technology. Research methodology: First, by reviewing previous studies and researches, the framework for readiness to accept blockchain was extracted. Then, the different areas of the value chain of knowledge-based organizations were identified. Then, a questionnaire for pairwise comparisons was distributed using a hierarchical approach. Finally, the TOPSIS questionnaire was distributed to rank the 5 identified areas of activity in the value chain and knowledge management of knowledge-based organizations. Semi-structured interviews with the organization's experts have been used to explain the promising methods in the organization further to improve the efficiency of blockchain acceptance and meaningful research orientations for researchers. Results: These findings include the undiscovered potential of knowledge sharing and collaboration networks, the expected evolutionary stages of the Internet of Things, and eliminating intermediaries that lead to new business models such as token building and short-term rather than long-term relationships. Obstacles include staffing problems, legal uncertainty, loss of infrastructure and standardization, and unclear governance structures. Improving smart contract security and interoperability between private and public protocols will further expand technolog Contribution: The application of blockchain technology in the field of knowledge and intellectual capital management, due to the promotion of key indicators such as improving security in the context of non-forgery, unchangeable information, tracking, decentralization, and transparency, leads to the application of this technology in knowledge and intellectual capital management.